The green workplace : sustainable strategies that benefit employees, the environment, and the bottom line - Stringer, Leigh (New York : Palgrave MacMillan, 2009)
As 21st century companies realize they'll need to be green to compete, sustainable ideas are spreading like wildfire throughout all fields of modern business. In this book, the author, an expert on sustainable workplace design and strategy, shows companies on the cusp of radically transforming their practices how to bring together diverse teams and establish new organizational governance for creative problem solving in greening their workplace. Her hands on green strategies are based on concrete and cost effective changes such as: working from home, ways to cut commuting costs, video conferencing to cut down on travel, increasing access to natural light to save energy, and more. She also explains how managers can implement these changes smoothly and efficiently. In solving key problems, she shows companies how a green business reduces costs, increases productivity, improves recruiting and retention, and increases shareholder value, in addition to benefiting the environment.
Includes bibliographical references and index.
Keywords: Industrial management -- Environmental aspects; Work environment; Organizational change; Sustainable development